In silico Pharmacological Evaluation of Tetrahydro-β-carboline Derivatives as Putative Inhibitors of Alpha-Synuclein and Dopa Decarboxylase for Parkinson’s Disease - Yao, Tham Xuan; Ayipo, Yusuf Oloruntoyin; Mordi, Mohd Nizam (Trends in Sciences, 2023)
Parkinson’s disease (PD) is a neurological problem that results mostly in disability globally due to therapeutic challenges. Alpha-synuclein (ASN) and Dopa decarboxylase (DDC) are strongly implicated in the pathogenesis of PD including the aggregation of Lewy bodies and degeneration of dopamine-producing cells. These make them plausible drug targets commonly explored by researchers in the quest for potent inhibitors. However, up to this moment, no inhibitor of ASN has been approved for clinical application while only a handful is available for DDC, as such, searching for effective inhibitors of the dual targets remains essential. In this study, the in-house databases of tetrahydro-β-carboline and carbazole derivatives were virtually screened for putative ligands with multitarget inhibitory mechanisms against the ASN and DDC using molecular docking protocols. Relevant drugs such as phenylbutyrate, anle138b, levodopa, carbidopa and benserazide were used as references. The physicochemical, pharmacokinetics, pharmacodynamics and toxicological profiles of the selected ligands and references were also evaluated in silico using pkCSM. From the virtual screening, ligands 172, 082 and 013 interacted more strongly with ASN receptors with SP glide gscores of –9.154, –9.124 and –8.971 kcal/mol respectively as compared to phenylbutyrate and anle138b with SP glide gscores of –7.181 and –5.875 kcal/mol. They also showed higher binding affinities to DDC receptor by higher SP glide gscores of –6.758, –5.212 and –6.271 kcal/mol than levodopa, carbidopa and benserazide with values of –4.217, –4.502 and –4.18 kcal/mol respectively. Among the 3 ligands, ligand 172 satisfies Lipinski’s Rules of 5 (RO5) and demonstrates ADMET parameters that favor a central nervous system (CNS) drug which was identified as potent inhibitors of ASN and DDC responsible for PD. The potential ligands with stronger inhibitory interactions and good ADMET profile are amenable for further experimental validation in the quest for potent inhibitors of ASN and DDC as anti-PD agents. HIGHLIGHTS Parkinson’s disease (PD) is a complex neurological disorder No effective medication has been approved for PD treatment Alpha-synuclein and dopa decarboxylase are relevant therapeutic targets Putative inhibitors are identified from tetrahydro-β-carboline (THBC) derivatives THBC derivatives deserve further studies as promising candidates for PD GRAPHICAL ABSTRACT